Pengaruh Literasi Keuangan Terhadap Keputusan Mahasiswa Menggunakan Produk Perbankan Syariah Pada Mahasiswa - Gunawan, Gempa; Syahriza, Rahmi; Kusmilawaty, Kusmilawaty (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Financial literacy is an important aspect in determining individual behavior in managing finances, including in choosing financial services that are in accordance with sharia principles. Among students, a good understanding of financial concepts and products can influence their decisions in using sharia banking services. This study aims to determine the effect of financial literacy on students' decisions in using sharia banking products. The method used is a quantitative approach with a simple linear regression analysis technique. Data were obtained by distributing questionnaires to 100 respondents. The results of the instrument testing showed that all items were valid and reliable with a Cronbach's Alpha value of 0.740 for financial literacy and 0.909 for usage decisions. The results of the simple linear regression analysis produced the equation Y = 17.917 + 2.047X. The hypothesis test showed a significant effect with a t_count value of 2.708, which is greater than the t_table of 1.66023, and a significance value of 0.001 which is below the threshold of 0.05. This finding indicates that every one unit increase in financial literacy will increase the decision to use Islamic banking products by 2,047 points. This study contributes theoretically by strengthening the discourse on financial literacy within the framework of Islamic economics and providing empirical evidence in the context of university students. Practically, it offers recommendations for higher education institutions and Islamic banking institutions in designing educational strategies and financial literacy enhancement programs to promote Islamic financial inclusion among the younger generation.